Model pemberdayaan ekonomi masyarakat miskin dengan penerapan Integrated Farming System (IFS) melalui pengelolaan dana zakat produktif di Kecamatan Gunung Kerinci - khori perdana; nurida isnaeni; Amri Amir (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this study is to produce a model of community economic empowerment in the Gunung Kerinci sub-district by implementing the Integrated Farming System (IFS) through the management of productive zakat funds. The analysis method used in this study is a qualitative descriptive method with a SWOT analysis tool. Poverty problems faced by the community in Gunung Kerinci District, especially farmers is to optimize land use by developing agricultural and livestock businesses by utilizing sources of productive Zakat funds and village funds managed in a farmer group located in every village in the province. Gunung Kerinci District with proper supervision and assistance. With optimal use of land, an integrated farming system can be applied, namely lowland rice and cattle which is expected to form a synergy between agriculture and animal husbandry that need each other and produce a more productive product that can lift the economy of the community, especially farmers.Based on the research, it is shown that people who receive productive zakat capital assistance are better able to develop their businesses than people who do not strengthen productive zakat. The work system in the field of product productivity and the most important part of the world of money and the development of the Gunung Kerinci system